2020
DOI: 10.3126/nmmj.v1i1.34469
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Of Three Different Regimens In Eradication Of Helicobacter Pylori Infection In Nepalese Patients Of Gandaki Region

Abstract: Background: Helicobacter pylori (H. pylori) is associated with the pathogenicity of gastro-duodenal ulcers and gastric cancers. Combination of several antimicrobial therapies and regimens have been advised for H. pylori treatment. But, resistance to various antibiotics regimens are being documented worldwide. The present study was undertaken to study the efficacy of commonly used 3 different regimens for eradication of H.pylori infection in Nepalese patients. Methods: A cross-sectional, hospital based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…A high eradication rate with levofloxacin-based therapy in the current study is consistent with studies by Dib et al 24 (94.8%) in Venezuelan population and Rakici et al 25 (92%) in Turkish population. In a prospective study by Bhattarai et al 21 conducted in similar setting as that of the current study, the eradication rate with levofloxacin-based therapy was found to be 77.8%. This could be possibly because the former study used levofloxacin-based therapy for 10 days only compared to 14 days in the current study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A high eradication rate with levofloxacin-based therapy in the current study is consistent with studies by Dib et al 24 (94.8%) in Venezuelan population and Rakici et al 25 (92%) in Turkish population. In a prospective study by Bhattarai et al 21 conducted in similar setting as that of the current study, the eradication rate with levofloxacin-based therapy was found to be 77.8%. This could be possibly because the former study used levofloxacin-based therapy for 10 days only compared to 14 days in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…20 In the observational study by Bhattarai et al in similar geographic set up, the eradication rate of 83.3% was reported with sequential therapy. 21 However, another prospective study in similar setting by Shrestha et al reported relatively better eradication rate (89%) with sequential therapy. 22 In a recent randomized controlled trial from India, the eradication rate with sequential therapy was found to be 92.9%, which is much higher than the current study.…”
Section: Discussionmentioning
confidence: 95%